2021
DOI: 10.1371/journal.pone.0254121
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon, physical fractions of the macro-organic matter, and soil stability relationship in lacustrine soils under banana crop

Abstract: Banana is a staple food and a major export commodity in the tropics. However, banana production systems are affected by the plant-soil relationships, where properties such as quality and quantity of soil organic matter play an important role in the dynamics of soil physical properties. In order to evaluate the effect of the soil organic carbon (SOC) content and its distribution in the water-stable of soil aggregates (WAS), and the physical fractions of the macro-organic matter, a study was conducted in lacustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In the last decade, the productivity of banana plantations in Venezuela has been affected mainly by the application of high-cost inputs including huge amounts of agrochemicals, and by soil conservation practices, generating a deterioration of the physical, chemical, and biological properties of soil [7,10]. Hence, the importance of evaluating these soil properties is linked to the decomposition of organic matter and the by-products that are generated by their determining role in the soil [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the productivity of banana plantations in Venezuela has been affected mainly by the application of high-cost inputs including huge amounts of agrochemicals, and by soil conservation practices, generating a deterioration of the physical, chemical, and biological properties of soil [7,10]. Hence, the importance of evaluating these soil properties is linked to the decomposition of organic matter and the by-products that are generated by their determining role in the soil [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques developed in our study can allow us to distinguish potentially suitable areas to obtain high levels of productivity and lead to long-term sustainability in these types of important areas. Studies of the CLQ developed in tropical areas [56,57], establish that commercial banana plantations in agricultural areas of the Venezuelan plains were characterized by a considerable reduction in the production and productivity due to a change and deterioration of the land. It was mainly caused by the physical, chemical and biological properties of the soil, these variables being the most determinant of the quality of banana soil in plains.…”
Section: Discussionmentioning
confidence: 99%
“…These location does not favor the rapid movement of water; such is the case of the high values of BD observed in some plots associated with their lake origin, which can affect the normal development of plant roots. Likewise, Rondon et al (2021) indicated that the physical variables of these soils of lacustrine origin, such as texture class, apparent density, porosity, and moisture retention capacity, were related to banana yield and productivity.…”
Section: Soil Physical Propertiesmentioning
confidence: 97%